2010
DOI: 10.1111/j.2042-7158.2010.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of fenofibrate dissolution delivered by a self-microemulsifying drug-delivery system

Abstract: The release rates of FFB from TPGS/Tween 20 systems were faster than those from TPGS/Tween 80 systems at the same K(m) value. In both systems, the release rates of FFB increased with a decrease in the K(m) value. Furthermore, both the release rates and the amounts of FFB from MDS in the water medium decreased with an increasing percentage of S(mix) added to both water contents. However, the release rates and amounts of FFB from MDSs increased with an increasing percentage of S(mix) in a 0.025 M sodium lauryl s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Although stirring rate is an important factor in dissolution testing, it is suggested that investigations related to mixing and agitation rates encountered in vivo also be conducted. [90][91][92][93][94][95][96] …”
Section: In Vitro Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although stirring rate is an important factor in dissolution testing, it is suggested that investigations related to mixing and agitation rates encountered in vivo also be conducted. [90][91][92][93][94][95][96] …”
Section: In Vitro Factorsmentioning
confidence: 99%
“…Furthermore, churning and agitation will differ based on the fed and fasted states; therefore, a closer inspection of the dissolution apparatus speeds and a better assessment of the agitation on dissolution also needs to be considered. [91][92][93][94][95][96] The presence of food will change the pH in the stomach; however, the changes are not uniform throughout the three distinct regions of the stomach (fundus, body, and antrum). 101,102 It was revealed that the gastric body and fundal pHs raised to a pH 4.5 in a time-dependent manner postfeeding, 101 whereas the antral pH remained at 2 throughout the time that food was present.…”
Section: In Vivo Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have demonstrated that enhanced drug release from SMEDDS could improve the bioavailability (6,(10)(11)(12)(13)(14)(15). However, SMEDDS is digestible and undergoes complicated structural changes in the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%